2019
DOI: 10.1089/gtmb.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Common Variants in the TLR-9 Gene and Hip Osteoarthritis Susceptibility

Abstract: Objective: Hip osteoarthritis (HOA) is one of the most common types of osteoarthritis and affects nearly 10% of men and 18% of women who are >60 years of age worldwide. It has been demonstrated to be a genetic disease with a 50% heritability risk. Recently, the TLR-9 gene has been associated with knee OA in both Turkish and Chinese populations, but the relationship between the TLR-9 gene and HOA has not been evaluated. In this study, we aimed to evaluate the relationship between the common genetic variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Although our study did not show an association with OA risk, several studies have found a positive association between TLR9 SNP rs187084 and susceptibility to OA [ 31 , 32 , 33 ]. Previous studies reported the T allele of rs187084 as associated with advanced stages of knee OA [ 31 ] and hip OA [ 18 ], while another study reported the C allele as a risk factor for knee OA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our study did not show an association with OA risk, several studies have found a positive association between TLR9 SNP rs187084 and susceptibility to OA [ 31 , 32 , 33 ]. Previous studies reported the T allele of rs187084 as associated with advanced stages of knee OA [ 31 ] and hip OA [ 18 ], while another study reported the C allele as a risk factor for knee OA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage deterioration in OA joints may be a consequence of TLR-ligand interactions with robust proinflammatory signaling [ 18 ]. TLR1, TLR2, TLR4, and TLR9 expression has been reported to be upregulated in OA chondrocytes [ 34 ], whereas TLR1-7 and TLR9 are upregulated in OA synovium [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated with psoriatic arthritis risk 69 , hip and knee osteoarthritis 70,71 , SLE 72 and IBD 73 ; associated with the risk of autoimmune thyroid disease 74 ; response to anti-TNF therapy in patients with RA 64 34 and DNA samples were obtained from peripheral blood collected at the Statens Serum Institut (Copenhagen, Denmark), which routinely perform screening for tuberculosis before treatment with biological treatments. Healthy blood donors were recruited in Viborg and Sønderborg (Denmark).…”
Section: Ra Patient Populationsmentioning
confidence: 99%
“…Several studies reported rs187084 (-1486, T>C) polymorphism of the TLR9 gene as a predisposing genetic marker for knee OA development in Chinese [53,54] and Turkish population [55]. The polymorphism rs187084 was also found to be significantly associated with hip OA risk [56].…”
Section: Role Of Cytokines In Oamentioning
confidence: 99%